Założenia europejskiego systemu walutowego - Komar, Andrzej (Wydział Prawa i Administracji UAM, 1986)
The article is devoted to the European monetary system instituted in Dec. 1978. It became a result of the long lasting search for stabilizing currency relations between member states of the European Community. Therefore, also the said search is discussed in consideration of the Treaty of Rome provisions of 1957. Particular emphasis wa slaid on theses of the Werner report on the economic-monetary union and of the Tindemans report on the European union. Much attention was focused on the so-called „currency serpent" which was mentioned in the both reports as a prerequisite to achieve the monetary stability. The initiative of Valéry Giscard d'Estaing and of Helmut Schmidt to constitute the European monetary system was indicated. The system was established by the decission of the European Council of Dec. 1978. The article discusses functions of the European monetary system and its specific parts. The evolution of clearing unit effected in the ECU (European Currency Unit) is presented. The way of calculating ECU, scope of its application is explained together with postulates to modify it and transform into a European currency. There are three types of crediting member states related to the monetary system as well as the system of currency intervention what can prove the range of monetary cooperation among the central banks of the Communities' member states. In the concluding remarks there are several postulates expressed as to improvements in functioning the European monetary system as well as reservations to the possibility of their realization.
Foundations of the European monetary system